Pemanfaatan Sumber Belajar Elektronik dan Lingkungan untuk Mendukung Pembelajaran - Shindy Aulia Afivatul Hasanah; Eva Yani; Moh Arya Nanda Ramadana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article aims to examine and explain the use of electronic learning resources and the environment to support the learning process. In preparing this article, the author used a literature study research method (library research), where the library literature used was in the form of articles and other relevant scientific works using Google Scholar and selecting several references that were appropriate to the topic of discussion. The results of preparing this article are as follows; (1) the use of electronic and environmental learning resources has several advantages and disadvantages compared to conventional learning resources such as being interesting, interactive and varied, (2) electronic and environmental learning resources can help increase learning effectiveness by increasing students' interest in learning, (3) The main challenge in using electronic learning resources and the environment is limited accessibility.